Analysis of Industrial Enterprises' Impact on Atmospheric Emissions - Mammadova Gulnara; Nuraliyeva Rahima; Dunyamalıyeva Hokume; Musayeva Sevil; Kholmurodova Dilafruz; Jumanov Alisher (BIO Web of Conferences)
The article analyzes the scientific basis and chemical properties of the environmental problem arising during production at industrial enterprises of the country, sources of its occurrence and damage to the environment. At Eini time, the minimization of emissions into the atmosphere by industrial enterprises, the econometric assessment of the impact of CO2 emissions per capita on CO2 emissions in the country, the development of environmental processes resulting from the development of the industry, ways to improve the protection of the environment and ways to eliminate the damage were analyzed.